Development of attitude and heading reference systems - Yen-Hsiang Huang; Rizal, Yusie; Ming-Tzu Ho (2015 International Automatic Control Conference (CACS), 2015)
The development of an attitude and heading reference system (AHRS) using sensor fusion is presented in this paper. The system consists of a nine degree of freedom inertial measurement unit (IMU) and a digital signal processor (DSP) module. The IMU comprises with triaxial gyroscopes, triaxial accelerometers, and triaxial magnetometers. By using the complementary filter, gain-scheduled complementary filter, and Kalman filter, the sensor fusion algorithms are implemented for the AHRS system. To verify the performance of the developed system, an experimental testbed of three-axis rotating platform is designed and constructed for experimental studies. It is shown that the robust performance can be obtained even though the system is in a dynamic state in the presence of a strong acceleration.